An Estimation of Technical Efficiency of Poultry Farming in Nepal - Pradhan, Nripesh Bahadur; Raut, Nirmal Kumar (Economic Journal of Development Issues, 2019)
The commercial poultry is growing rapidly in Nepal which requires that efficient level of output that ensures high levels of productivity and profit is produced. The objective of this study is to estimate the technical efficiency of the poultry farming in Nepal and its distribution spatially across the districts. The study utilizes Cobb-Douglas production function to define the structure of the production model and its error term is assumed to follow exponential distribution. Thereafter, using maximum likelihood estimator, parametric approach to Stochastic Frontier Method is applied to the data obtained from Nepal Commercial Poultry Survey 2015. The study finds technical efficiency of 92 percent suggesting high efficiency. Assuming half-normal distribution in the error term, however, yields technical efficiency of 89 percent. Further disaggregation of technical efficiency by districts shows its homogenous distribution across the districts covered in the study. The study, hence, suggests the possibility to increase its production to the level of potential output by improving technical efficiency. One of the various ways to improve technical efficiency is by ensuring high quality inputs both physical and technical to the poultry farms.